2019
DOI: 10.1016/j.tet.2019.130639
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high pressure direct syntheses of bis(imidazolium-3-yl)alkane dichlorides

Abstract: Ultra-high pressure direct syntheses of bis(imidazolium-3yl)alkane dichlorides. Tetrahedron, 75 (44). 130639.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Alkylations with dichloroethane (DCE) are infrequently realized due to its marked electronic deactivation, but DCE provides an economically attractive source of the chloroethyl group to access ethylene-(bis-imidazolium) dictations. Moderate yields of the dication were obtained in previous reports after refluxing for 24 h in chloroform, but the reaction can be improved under high (1.95 GPa) pressure . Reacting NMI with DCE (2 eq.)…”
Section: Resultsmentioning
confidence: 99%
“…Alkylations with dichloroethane (DCE) are infrequently realized due to its marked electronic deactivation, but DCE provides an economically attractive source of the chloroethyl group to access ethylene-(bis-imidazolium) dictations. Moderate yields of the dication were obtained in previous reports after refluxing for 24 h in chloroform, but the reaction can be improved under high (1.95 GPa) pressure . Reacting NMI with DCE (2 eq.)…”
Section: Resultsmentioning
confidence: 99%
“…Some examples have shown that hyperbaric conditions strongly favor these reactions, and recently it was reported that N -substituted imidazoles 211 reacted with α,ω-dichloroalkanes 212 under 19 kbar to give a wide variety of bis(imidazoliumyl)alkanes 213 in a one-pot process (Scheme 68). 124 The crucial role of pressure is confirmed by the fact that this reaction proceeds very slowly at ambient pressure; in some cases, no conversion is observed even after 120 h. At the same time, the target salts are usually formed in quantitative yields at 19 kbar after 24 h. However, the most congested imidazoles 211 require more time, and generally complete within 2–3 days at 19 kbar. An increase in steric hindrance around the imidazole nucleus leads to a decrease in yields in the following order: 1-methylimidazole > 1,2-dimethylimidazole > 1,2,4,5-tetramethylimidazole > 1-methyl-2-phenyl imidazole.…”
Section: Substitution Reactions At High Pressurementioning
confidence: 98%
“…While bis­(azolium) dichloride salts are widely used in organic and organometallic chemistry, their efficient access from N -substituted imidazoles has been seriously impeded by the poor electrophilicity of 1,1-dichloroalkanes such as dichloromethane in nucleophilic substitution processes . Indeed, known routes to access these salts typically lack generality and practicality, requiring either prolonged heating in PEG 200 as solvent (Scheme a) or the use of an ultra-high pressure apparatus (Scheme b), where yields were found to drastically decrease with longer N -alkyl substituents. After taking a closer look at these procedures, we noted that a common feature involves the use of stoichiometric dichloromethane as an electrophile rather than a large excess, presumably to avoid isolation of the monoalkylated N -chloromethyl imidazolium intermediate instead of the desired bis­(azolium) salt. ,, Due to the poor electrophilicity of dichloromethane, these reactions are often run at temperatures well above its boiling point in sealed vessels to prevent loss of this limiting reagent during the reaction, making the procedures difficult to reproduce on different scales.…”
mentioning
confidence: 99%
“…Indeed, known routes to access these salts typically lack generality and practicality, requiring either prolonged heating in PEG 200 as solvent (Scheme a) or the use of an ultra-high pressure apparatus (Scheme b), where yields were found to drastically decrease with longer N -alkyl substituents. After taking a closer look at these procedures, we noted that a common feature involves the use of stoichiometric dichloromethane as an electrophile rather than a large excess, presumably to avoid isolation of the monoalkylated N -chloromethyl imidazolium intermediate instead of the desired bis­(azolium) salt. ,, Due to the poor electrophilicity of dichloromethane, these reactions are often run at temperatures well above its boiling point in sealed vessels to prevent loss of this limiting reagent during the reaction, making the procedures difficult to reproduce on different scales. While the kinetic profiles of these transformations are not well-known, analogous processes involving pyridine derivatives as nucleophiles have previously been thoroughly investigated (eq ).…”
mentioning
confidence: 99%
See 1 more Smart Citation